Obliczanie masy wody towarzyszącej przy drganiach poprzecznych silników okrętowych - WIĘCKOWSKI, Józef (Engineering Transactions, 1957)
Computation of the added mass of water during transverse vibration of a marine engineBased on the equations of plane potential flow of an ideal liquid, a computation. is made surface density of the apparent added mass of water during transverse vibration of a marine engine, assuming infinitely high frequency of water particles and disregarding the influence of free waves.A numerical example illustrates the calculations for an elliptical contour, assuming the values of the geometrical and mechanical parameters characterizing the contour from real steel ,cutters.A comparison of the values obtained for the density of the added mass of water, with approximate values according to O. Grimm, [1], has shown the necessity of accurate calculation.Finally, problems connected with transverse vibrations of engines are discussed in the light of the results of vibration measurements, [8], for steel cutters.